The artificial sand x natural sand for concrete production - Barbosa, Maria Teresa Gomes (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This research with the objective of finding aggregate that it comes, totally, they substitute the primary natural material of rivers, it is increasing because that has been causing severe environmental impacts. This research deals with recycling of the left over residue from processing of ornamental stones known as residue from the marble cutting process and gnaisse cutting process. The experimental program consisting in analyzing the physical and the mechanical properties of the residue and of the concrete, respectively, it will be present in that work. The tests indicate the better residue’s properties than natural sand for concrete production.